Study smart: Peer-teaching workshop series for learning strategies, time and stress management in medical studies – a project report - Gross, Georg; Feron, Leon; Beetz, Felix; Krapp, Nicolas; Schüttpelz-Brauns, Katrin (GMS Journal for Medical Education)
Introduction: Studying medicine places high demands on students' learning behavior. Nevertheless, most medical faculties in German-speaking countries do not offer curricular training for the acquisition of key learning skills. The aim of the project was to develop a series of workshops on evidence-based learning strategies, time and stress management. Project description: The “study smart” workshop series was developed by students of the Mannheim Medical Faculty in 2018. Participants learn evidence-based techniques for long-term knowledge acquisition, self-, time- and stress management. Due to high demand, the workshop was subsequently incorporated as a permanent component of the curriculum. Since 2021, “study smart” has been a project of the German Medical Students’ Association. Once yearly, students from other faculties are trained at a peer-training-weekend. In total, the workshop series was offered at 8 faculties and several times online. In 2021, a one-off survey of medical students was also conducted at the Medical Faculty Mannheim two months after the workshop series. Results: A total of 68 workshop participants and 72 non-participants took part in the survey. This showed a more frequent use of the “active recall” learning strategy, in particular the “anki” flashcard program (14 (33%) of participants vs. 4 (10%) of non-participants; p=0.009). Participants reported creating Anki decks, which are shared with the entire class and revised together. In total, over 1000 medical students across Germany have participated in the workshop series over the past 5 years. Discussion: Student interest in the workshop series remains high. Study Smart has become a widely utilized and highly regarded program. In the assessment of satisfaction with their own learning strategies, there was no significant difference between participants and non-participants. There are also challenges in the long-term implementation of the workshops at medical faculties at other universities due to a high turnover of peer teachers. The national project coordinator is therefore working on establishing local group networks.